Monotone Iterative Schemes for Positive Solutions of a Fractional q-Difference Equation with Integral Boundary Conditions on the Half-Line - Min Jiang; Rengang Huang (Journal of Mathematics)
In this paper, we study the boundary value problem of a fractional q-difference equation with nonlocal integral boundary conditions on the half-line. Using the properties of the Green function and monotone iterative method, the extremal solutions are obtained. Finally, an example is presented to illustrate our main results.